Synthesis of pyridazinones via molecular-iodine-mediated cleavage of 4-bromomethylcoumarin precursors. Issue 21 (1st November 2016) - Shamala, Devadas; Shivashankar, Kalegowda
ABSTRACT: A facile and an efficient protocol for the synthesis of pyridazinones via molecular-iodine-mediated cleavage of 4-bromomethylcoumarin precursors in the presence of I2 in ethanol at 70 °C is reported. The present approach replaced the basic condition (K2 CO3 ) with Lewis acidic condition. GRAPHICAL ABSTRACT: